Perancangan Aplikasi E-Commerce Untuk Meningkatkan Penjualan Kain Tenun Ikat Fanny Art Shop - Witi, ferdinandus Lidang; Yosep D. Da Yen Khwuta; Thomas E. D. Marang (Teknik Komputer Politeknik Negeri Sriwijaya, 2023)
Fanny Art shop is a business engaged in the sale of woven fabrics typical of NTT. At present the sales process that runs at the fanny art shop is face to face or the buyer must come directly to the shop, and also product marketing at the Fanny Art shop is still relatively minimal because they still use social media such as Facebook and Instagram, this causes only only a handful of people can view sales posts. This is motivated by the rapid development of information technology and the large number of business people who market their products through E-commerce as a medium for online sales. Therefore, a promotional media and online sales based on an e-commerce website for the sale of woven textiles were designed. This design and manufacture is intended to facilitate sales and promotions, as well as to make it easier for consumers to choose East Nusa Tenggara woven woven models, without having to come to the shop in person, especially during the Covid-19 pandemic. In the process of developing this E-Commerce website using the Php and Mysql programming languages and the technique used is waterfall. The data flow method used is a structured method consisting of Data Flow Diagrams (DFD) to describe the functional model and Entity Relationship Diagram (ERD) to describe the data model as well as the testing technique using Blackbox testing. The goal to be achieved from developing this E-Commerce Web is to make it easier for buyers to make transactions wherever the buyer is without having to come directly to the Fanny Art Shop.